EVALUASI FUNGSI TERMINAL TYPE “C” DI KABUPATEN MIMIKA - Muhammad Zakaria; Yahya Nusa (CV. Adiba Aisha Amira, 2024)
This research aims to determine the suitability of the Mimika Regency Type C terminal facilities with Type C Terminal standards based on the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 24 of 2021 and to determine the suitability of services at the Type C Terminal of Mimika Regency in accordance with the Service Standards of the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 40 of 2015. This research is descriptive research using a qualitative approach. Based on the results of the analysis, it is known that the Mimika Regency Type C Terminal facilities do not comply with the standards of the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 24 of 2021 concerning the operation of road transport passenger terminals and the services provided by Mimika Regency Type C Terminal officers do not meet the standards of the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 40 of 2015 concerning service standards for the operation of road transport passenger terminals